Human erythrocyte remodelling during Plasmodium falciparum malaria parasite growth and egress - Mbengue, Alassane. (2013)
The intra-erythrocyte growth and survival of the malarial parasite Plasmodium falciparum is responsible for both uncomplicated and severe malaria cases and depends on the parasite's ability to remodel its host cell. Host cell remodelling has several functions for the parasite, such as acquiring nutrients from the extracellular milieu because of the loss of membrane transporters upon erythrocyte differentiation, avoiding splenic clearance by conferring cytoadhesive properties to the infected erythrocyte, escaping the host immune response by exporting antigenically variant proteins at the red blood cell surface. In addition, parasite-induced changes at the red blood cell membrane and sub-membrane skeleton are also necessary for the efficient release of the parasite progeny from the host cell. Here we review these cellular and molecular changes, which might not only sustain parasite growth but also prepare, at a very early stage, the last step of egress from the host cell.